Inspiratory muscle training protocol for patients with chronic obstructive pulmonary disease (IMTCO study): a multicentre randomised controlled trial. Issue 8 (5th August 2013) - Charususin, Noppawan; Gosselink, Rik; Decramer, Marc; McConnell, Alison; Saey, Didier; Maltais, Francois; Derom, Eric; Vermeersch, Stefanie; van Helvoort, Hanneke; Heijdra, Yvonne; Klaassen, Mariska; Glöckl, Rainer; et al.
Abstract : Introduction: Inspiratory muscle training (IMT) has been applied during pulmonary rehabilitation in patients with chronic obstructive pulmonary disease (COPD). However, it remains unclear if the addition of IMT to a general exercise training programme leads to additional clinically relevant improvements in patients with COPD. In this study, we will investigate whether the addition of IMT to a general exercise training programme improves 6 min walking distance, health-related quality of life, daily physical activity and inspiratory muscle function in patients with COPD with inspiratory muscle weakness. Methods and analysis: Patients with COPD (n=170) with inspiratory muscle weakness (Pi, max <60 cm H2 O or <50%pred) will be recruited to a multicentre randomised placebo controlled trial of IMT and allocated into one of the two groups. Patients in both groups will follow a 3 month general exercise training programme, in combination with home-based IMT. IMT will be performed with a recently developed device (POWERbreathe KH1). This device applies an inspiratory load that is provided by an electronically controlled valve (variable flow resistive load). The intervention group (n=85) will undertake an IMT programme at a high intensity (≥50% of their Pi, max ), whereas the placebo group (n=85) will undertake IMT at a low training intensity (≤10% of Pi, max ). Total daily IMT time for both groups will be 21 min (6 cycles of 30 breaths). Improvement in the 6 min walking distance will be the primary outcome. Inspiratory muscle function, health-related quality of life and daily physical activity will be assessed as secondary outcomes. Ethics and dissemination: Ethics approval has been obtained from relevant centre committees and the study has been registered in a publicly accessible clinical trial database. The results will be easily interpretable and should immediately be communicated to healthcare providers, patients and the general public. Results: This can be incorporated into evidence-based treatment recommendations for clinical practice. ClinicalTrials.gov: NCT01397396.